2007
DOI: 10.1002/ijc.22462
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lung carcinogenesis by 1α,25‐dihydroxyvitamin D3 and 9‐cis retinoic acid in the A/J mouse model: Evidence of retinoid mitigation of vitamin D toxicity

Abstract: 9-cis-Retinoic acid (9cRA) and 1a, 25-dihydroxyvitamin D 3 (1,25D) show promise as potential chemopreventive agents. We examined 9cRA and 1,25D, alone and in combination, for their potential to inhibit carcinogen (NNK)-induced lung carcinogenesis in A/J mice. A/J mice (n 5 14/group) were treated with 9cRA (7.5, 15, or 30 mg/kg diet), 1,25D (2.5 or 5.0 lg/kg diet), or a combination of 9cRA (15 mg/kg diet) plus 1,25D (2.5 lg/kg diet) for 3 weeks before and 17 weeks after carcinogen injection. Lung tumor inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…Sundar et al [25] have suggested that the lack of vitamin D receptor activates pathways that are associated with pathogenesis of chronic obstructive pulmonary disease. A study in a mouse model of lung cancer found that vitamin D supplementation decreased tumor incidence [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Sundar et al [25] have suggested that the lack of vitamin D receptor activates pathways that are associated with pathogenesis of chronic obstructive pulmonary disease. A study in a mouse model of lung cancer found that vitamin D supplementation decreased tumor incidence [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Tobacco smoke chemicals may influence vitamin D metabolism and function (8 -10 ), and conversely vitamin D may modify the carcinogenicity of tobacco smoke chemicals (3,(11)(12)(13)(14). Such studies led the International Agency for Research on Cancer to suggest that the effect of tobacco smoke on vitamin D may explain a component of the carcinogenicity conferred by smoking (15 ); however, evidence from later nested case control and prospective cohort studies regarding individual tobacco-related cancers has been conflicting (16 -23 ).…”
mentioning
confidence: 99%
“…Vitamin D insufficiency is a global health problem and is associated with a number of illnesses [4,5]. Vitamin D also has been suggested to have important roles against cancer development, and it has anti-tumor effects [6,7]. Previous epidemiological studies have suggested that vitamin D is associated with decreased risks of colorectal cancer, and breast cancer [4,8].…”
Section: Introductionmentioning
confidence: 99%